2018
DOI: 10.2147/jpr.s164774
|View full text |Cite
|
Sign up to set email alerts
|

Trends and patterns of analgesic prescribing in Malaysian public hospitals from 2010 to 2016: tramadol predominately used

Abstract: PurposeTo examine the trends of analgesic prescribing at public tertiary hospital outpatient settings and explore the patterns of their utilization in nonsteroidal anti-inflammatory drugs (NSAIDs), tramadol, and opioid patients.Patients and methodsThis cross-sectional study was conducted from 2010 to 2016 using the prescription databases of two tertiary hospitals in Malaysia. Prescriptions for nine NSAIDs (ketoprofen, diclofenac, celecoxib, etoricoxib, ibuprofen, indomethacin, meloxicam, mefenamic acid, and na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
12
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 28 publications
5
12
1
1
Order By: Relevance
“…The most frequently prescribed pharmacological group was non-opioid analgesics, which is in line with the recommendations of clinical practice guidelines [ 4 , 6 , 9 ] previously reported in other works [ 5 , 18 , 22 ]. The most commonly used analgesic was acetaminophen, similar to what has been published in other studies [ 16 , 23 ], followed by NSAIDs.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The most frequently prescribed pharmacological group was non-opioid analgesics, which is in line with the recommendations of clinical practice guidelines [ 4 , 6 , 9 ] previously reported in other works [ 5 , 18 , 22 ]. The most commonly used analgesic was acetaminophen, similar to what has been published in other studies [ 16 , 23 ], followed by NSAIDs.…”
Section: Discussionsupporting
confidence: 86%
“…The most commonly used analgesic was acetaminophen, similar to what has been published in other studies [16,23], followed by NSAIDs. The most commonly used NSAID in this report was naproxen, and its rate of use was very high compared with the rates reported in other studies (25.4% vs. 1.6-8.0%) [5,24,25]; however, in other countries, other active principles predominate, such as diclofenac (Iran: 49.2%, and India: 22.8%) [24,26], acetylsalicylic acid (Nigeria: 62.2%) [25], nimesulide (Italy: 20.0%) [15], and ketoprofen (Malaysia: 17.5%) [5]. The proportion of prescription of COX-2 selective NSAIDs has been demonstrated to be low in different studies [17,25,26], similar to the findings of this report, probably due to its cardiovascular safety problems and its association with various adverse reactions [7].…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Age is closely associated with increased opioid use [ 24 ]. Studies from European countries between 2000 and 2010 reported that the utilization of strong opioids was highest among patients aged 66-80 years [ 21 , 25 ]. A study from Malaysia showed that opioid prescriptions increased with patient age (11% in the 40s, 19% in the 50s, and 47.28% in the 60-80s) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%